Review of grain threshing theory and technology - Fu, Jun; Chen, Zhi; Han, Lujia; Ren, Luquan (International Journal of Agricultural and Biological Engineering, 2018)
Threshing is the most important function of grain harvester. Grain loss and damage in harvesting are significantly related to threshing theory and technology. There are four kinds of threshing principles including impact, rubbing, combing and grinding. Four types of contact models between grain and threshing components have been constructed correspondently. Grain damage can be regarded as a function of peripheral velocity and contact pattern of impacting. Grain loss can be regarded as a function of contact pattern of rasp bars. Grain loss coming from cleaning and separation in the subsequent process of combing threshing was significantly decreased. Tangential and axial threshing technologies have been applied in grain threshing system widely. It showed that in the combined application, tangential rolls are used to accelerate grain flow, and axial rolls are used to increase threshing quality especially lower loss and damage. Conical concave may take the place of the traditional cylindrical one. With the development of sensor technology and communication technology, intelligent harvesting robot and automatic threshing system will be integrated together to improve grain quality and operation comfort.Keywords: grain, threshing, threshing theory, threshing technology, harvester, grain lossDOI: 10.25165/j.ijabe.20181103.3432Citation: Fu J, Chen Z, Han L J, Ren L Q. Review of grain threshing theory and technology. Int J Agric & Biol Eng, 2018; 11(3): 12–20.